Biological features and trophic specialization of the acorn moth Blastobasis glandulella (Riley, 1871) (Blastobasidae) in the Western Podillia - Соколова, І. М. (Forestry and Forest Melioration, 2024)
Introduction Blastobasis glandulella (Riley, 1871) (Blastobasidae (Meyrick, 1894)) originates from the eastern United States and southern Canada. Larvae develop in acorns of different species of Quercus L. and fruits of Castanea Mill. and Carya Nutt. B. glandulella has been known in Europe since the early 80s and has spread to 16 countries. It was first identified in Ukraine in 2009 in Transcarpathia. The phenology of B. glandulella has not yet been investigated. In 2022, researchers of the Department of Entomology, Phytopathology, and Physiology in Ukrainian Research Institute of Forestry and Forest Melioration analyzed acorns from various regions of Ukraine. They found the pest in the acorns collected in Kyiv, Cherkasy, Poltava, Khmelnytskyi, and Ternopil regions. Preliminary analysis of the material showed that in the east of the Ternopil region and the southwest of Khmelnytskyi region, the acorn moth formed stable populations and damaged many acorns. Therefore, the study of this alien species was carried out in Western Podillia. This research aimed to clarify the specifics of acorn moth development and its host plants in Western Podillia. Materials and Methods Our research was carried out in the forest stands and in the laboratory. Phenological observations and collection of fruits for subsequent analysis and rearing to adults were carried out at eight locations in the Kamianets-Podilskyi district of Khmelnytskyi region and Chortkivskyi district of Ternopil region. Acorns and fruits of Aesculus sp. and Juglans sp. were collected from late fall to early spring. In the laboratory, the entrance and exit holes in fruits were recorded. Then the fruits were cut to record larvae, pupae, excrement, etc. A total of 2,240 acorns of various oak species, 260 horse chestnut fruits, and 250 nuts were analyzed. A method for acorn moths rearing from larvae found in fruits has been developed and tested. To study the moth phenology, in the field, from March to October at least 50 acorns were collected and analyzed from one location. The pupation and moth emergence dates were recorded in natural conditions. To determine the dates of egg hatching, the fruits were collected from the beginning of July. Results and Conclusions It was found that, besides acorns of various oak species (Quercus robur L., Q. rubra L., Q. castaneifolia C. A. Mey), caterpillars of the acorn moth develop in the fruits of Aesculus hippocastanum L., A. parviflora Walt., A. glabra Willd. and some Juglans sp. (Juglans cinerea L. and J. regia L.). A caterpillar has a long lifespan, overwinters inside the fruits, and completely consumes their cotyledons. As one acorn (fruit) is consumed, the caterpillar crawls to another, damaging several fruits before pupation, which lose their viability. The larvae pupate inside or outside the fruit, or on the forest floor, from April to mid-September. B. glandulella prevents seed regeneration of forests, obtaining oak, walnut, and horse chestnut seeds, and planting material for forest and urban stands. 10 Figs., 1 Table, 18 Refs.